Bone Marrow Edema, Clinical Significance, and Treatment Options: A Review. Issue 20 (15th October 2020) - Akhavan, Sam; Martinkovich, Stephen C.; Kasik, Connor; DeMeo, Patrick J.
Abstract : Bone marrow edema (BME) is a descriptive term used to describe high-signal intensity changes detected on magnetic resonance fluid-sensitive sequences that could be attributed to a number of underlying pathologies. Regardless of the cause, physiologic remodeling of the subchondral bone can be limited because of ongoing joint forces, increased focalization of stress, and reduced healing capacity of the subchondral bone. BME is a known prognostic factor associated with pain, dysfunction, and progressive cartilage damage. This review summarizes the current known causes of BMEs, theories related to histopathological changes, and current treatment options including novel biologic surgical options.